The Effect of Motivational Interviewing on Adolescent Life Skill Toward Risky Behaviors in Indonesia: A Queasy Experimental Design - Yosep, Iyus; Mardhiyah, Ai; Tram, Nguyen Thi Bich (STIKep PPNI Jawa Barat, 2025)
Background: Adolescents are vulnerable to engaging in risky behaviors that compromise their health. Motivational interviewing (MI) is a brief intervention that can promote positive behavior changes. Objectives: This study aimed to examine the effect of MI on adolescent life skills related to risky behavior prevention in Indonesia. Methods: A quasi-experimental design with a pre-test/post-test control group was conducted between April and May 2021. The intervention group received five weekly MI counseling sessions (30–45 minutes each). Life skills were assessed using the Life Skill Training Questionnaire for High School Students (LSTQ-HS). An ANCOVA test was used to compare post-intervention scores between groups, controlling for baseline differences. Results: The intervention group’s total life skills score significantly increased from 94.57 (SD=14.06) to 117.80 (SD=4.71) (p<0.001). Significant improvements were also observed across refusal skills, assertiveness, relaxation, and self-control (p<0.05). ANCOVA analysis confirmed a significant difference between the intervention and control groups post-intervention (F=94.82, p<0.001). Conclusions: Motivational interviewing effectively enhanced adolescents' life skills related to risky behavior prevention. Integrating MI into school-based life skills programs may support adolescent health. Future studies with rigorous designs and larger sample sizes are recommended to strengthen these findings.